2008
DOI: 10.1016/j.biochi.2008.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of human telomeric quadruplex structures

Abstract: Human telomeric DNA consists of tandem repeats of the sequence d(TTAGGG). Compounds that can stabilize the intramolecular DNA G-quadruplexes formed in the human telomeric sequence have been shown to inhibit the activity of telomerase and telomere maintenance, thus the telomeric DNA G-quadruplex has been considered as an attractive target for cancer therapeutic intervention. Knowledge of intramolecular human telomeric G-quadruplex structure(s) formed under physiological conditions is important for structure-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
417
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(443 citation statements)
references
References 80 publications
(172 reference statements)
18
417
0
3
Order By: Relevance
“…[58,90] It is important to note, however, that G-quadruplexes are highly dynamic structures and losses in DNA conformational entropy upon ligand binding might be an important factor in determining specificity. G-quadruplexes that exist as a dynamic mixture of conformations in the unbound state, like the human telomeric sequence, [91] should generally exhibit lower ligand affinities as compared to G-quadruplexes that adopt a single conformation. [58,90] While a large number of G-quadruplex ligands have been reported in the literature, [41,42,46,89,[92][93][94] the cationic porphyrin TMPyP4 (Fig.…”
Section: Some Known G-quadruplex Ligands and Their Activitiesmentioning
confidence: 99%
“…[58,90] It is important to note, however, that G-quadruplexes are highly dynamic structures and losses in DNA conformational entropy upon ligand binding might be an important factor in determining specificity. G-quadruplexes that exist as a dynamic mixture of conformations in the unbound state, like the human telomeric sequence, [91] should generally exhibit lower ligand affinities as compared to G-quadruplexes that adopt a single conformation. [58,90] While a large number of G-quadruplex ligands have been reported in the literature, [41,42,46,89,[92][93][94] the cationic porphyrin TMPyP4 (Fig.…”
Section: Some Known G-quadruplex Ligands and Their Activitiesmentioning
confidence: 99%
“…However compounds that stabilize the telomeric G-quadruplex have been shown to inhibit the activity of telomerase and disrupt telomere capping and maintenance, making the human telomeric DNA G-quadruplex also an attractive target for cancer therapeutic intervention (Mergny & Helene, 1998;Riou et al, 2002;Gowan et al, 2001;de Cian et al, 2008). Indeed, the intramolecular telomeric G-quadruplex (Neidle & Parkinson, 2003;Dai et al, 2008) has been considered to be an attractive target for anticancer drug design since quadruplex ligands were found to inhibit telomerase (Sun et al, 1997;Zahler et al, 1991;Zaug et al, 2005). However genomic analyses using several algorithms have revealed that more than 370 000 sequences have the potential to form G-quadruplex structure in the human genome Huppert, 2008).…”
Section: Telomeric G-quadruplexes Are New Targets For Cancer Therapymentioning
confidence: 99%
“…However, this result might be an underestimation of this binding because not all the decays can be detected by this method. In vitro studies have indicated the polymorphic nature of the telomeric G-quadruplex (Dai et al, 2008), and the 3 H-360A ligand may therefore be unable to bind all the G-quadruplex structural conformations. In addition, 3 H-360A is naturally unstable due to progressive radiolysis, so we cannot totally exclude a partial degradation of this G-quadruplex ligand.…”
Section: In Vivo Binding Of G-quadruplex Ligand 360amentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, K + is essential to fold and stabilize G-quadruplexes (23). Agents that stabilize or target G-quadruplexes may act as anti-tumor agents (24); thus, physiological concentrations of K + are likely to be required for normal cell behavior (25,26). K ascorbate has been proposed as an anti-degenerative agent (27).…”
Section: Introductionmentioning
confidence: 99%